القيود الواردة على سلطة القاضي في الاجتهاد القضائي: فرنسا أنموذجا - حسن، حيدر فليح (جامعة زيان عاشور الجلفة, 2021)
يخضع القضاة عند ممارستهم لسلطتهم في الاجتهاد القضائي لجملة من القيود التي يتعين عليهم التقيد بها إذ ما أرادوا لاجتهادهم أن يحظى بالمقبولية والترحاب من قبل المشتغلين بالقانون بصورة عامة، وفقهاء القانون بشكل خاص، وبخلافه فإن سهام النقد والتجريح ستطال تلك الاجتهادات، وعندها سيتعين عليهم العدول عنها. ولعل أهم تلك القيود المفروضة على القضاة هي مراعاتهم للعدالة بين أطراف الدعوى من خلال عدم تحيزهم لأحد الأطراف على حساب الطرف الأخر، إلى جانب مراعاتهم للنظام العام والآداب العامة، فضلا عن مراعاتهم للنصوص القانونية الذي يعملون تحت مظلتها، وأخيرا وليس آخرا مراعاتهم للحقوق والحريات الأساسية للأفراد والتي نصت عليها المواثيق الدولية فضلا عن القوانين الوطنية.
When exercising their authority in the jurisprudence, judges are subject to a set of restrictions that they must adhere to, as they do not want their jurisprudence to be accepted and welcomed by law practitioners in general, and legal scholars in particular, and in contrast to it, the arrows of criticism and defamation will extend to that jurisprudence, and then they will have to reverse them . Perhaps the most important of those restrictions imposed on judges is their observance of justice between the parties to the lawsuit through their lack of bias for one of the parties at the expense of the other, in addition to their observance of public order and public morals, as well as their observance of the legal texts that they work under its umbrella, and last but not least their respect for the rights and fundamental freedoms of individuals As stipulated in international conventions as well as national laws.
Keywords: القانون المدني -- النصوص القانونية -- الاجتهاد القضائي -- القانون الفرنسي